Jaramillo, Samuel (2009), Hacia una teoría de la renta del suelo urbano, Bogotá, Universidad de Los Andes - Schteingart, Martha (Estudios Demográficos y Urbanos, 2012)
Jaramillo, Samuel. (2009). Hacia una teoría de la renta del suelo urbano, Bogotá, Universidad de Los Andes.